Analysis of Promotional Strategy, Product Quality, and Price Perception on Purchasing Decisions (A Study on Consumers at Cililitan Wholesale Center) - Wau, Pilipus; Yanthy Yosepha, Sri (Dinasti Publisher, 2025)
The consumer purchasing decision plays a crucial role in business success, including at the Cililitan Wholesale Center, one of the largest shopping centers in Jakarta. This study aims to analyze the impact of promotional strategies, product quality, and price perception on consumer purchasing decisions at the Cililitan Wholesale Center. Using a quantitative approach with a descriptive design, data were collected through a questionnaire survey from 200 randomly selected respondents. The results of multiple linear regression analysis indicate that product quality (p-value = 0.000) has the most significant influence on purchasing decisions, followed by promotional strategies (p-value = 0.002) and price perception (p-value = 0.015). These findings suggest that product quality plays a primary role in attracting consumer purchase interest, while promotional strategies and price perception also contribute significantly. The study recommends that the Cililitan Wholesale Center continue to improve product quality and implement effective promotional strategies, as well as consider consumer price perceptions when formulating pricing policies.